Study of Bc → J/ψV and Bc*⃗ηcV decays within the QCD factorization. (12th June 2018) - Chang, Qin; Chen, Li-Li; Xu, Shuai
Abstract: In this paper, we study the non-leptonic B c → J / ψV and B c * → η c V ( V = ρ, K * ) weak decays in the framework of QCD factorization. In the evaluation, the form factors are calculated using the Bauer–Stech–Wirbel model and the light-front quark model, respectively. Besides the longitudinal amplitude, the power-suppressed transverse contributions are also evaluated at next-to-leading order. The predictions for the observables of B c → J / ψV and B c * → η c V decays are presented. We find that the NLO QCD contribution presents about 8% correction to the branching ratios, and the longitudinal polarization fractions of these decays are at the level of (80 ∼ 90)%. In addition, we suggest direct measurements on some useful ratios, R K * / ρ ( λ = 0 ) and R ̃ K * / ρ ( λ = 0 ), which are very suitable to test the consistence between theoretical prediction and data because their theoretical uncertainties can be well controlled.